2022
DOI: 10.3389/fpls.2022.991557
|View full text |Cite
|
Sign up to set email alerts
|

Neurofuzzy logic predicts a fine-tuning metabolic reprogramming on elicited Bryophyllum PCSCs guided by salicylic acid

Abstract: Novel approaches to the characterization of medicinal plants as biofactories have lately increased in the field of biotechnology. In this work, a multifaceted approach based on plant tissue culture, metabolomics, and machine learning was applied to decipher and further characterize the biosynthesis of phenolic compounds by eliciting cell suspension cultures from medicinal plants belonging to the Bryophyllum subgenus. The application of untargeted metabolomics provided a total of 460 phenolic compounds. The bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The injection volume was 12 µL, and each sample analysis was repeated twice (n = 6). For compound detection, the mass spectrometer operated in positive polarity and SCAN mode, and the extended dynamic range mode was set at 100–1200 m/z and a nominal resolution of 40,000 FWHM [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The injection volume was 12 µL, and each sample analysis was repeated twice (n = 6). For compound detection, the mass spectrometer operated in positive polarity and SCAN mode, and the extended dynamic range mode was set at 100–1200 m/z and a nominal resolution of 40,000 FWHM [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Once annotated, the compounds were filtered in relation to their abundance, only selecting those detected in 66.6% of the replicates within each treatment. The detected phenolic compounds were grouped into different families and subfamilies and quantified through calibration curves obtained with reference standards for each class, as previously indicated [ 14 ]. Tyrosol was selected as the reference standard of low-molecular-weight phenols (LMW), including alkylphenols, coumarins, phenylpropenes, quinones, tyrosols, and other phenolics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors observed that the combination of both factors resulted in an increase of more than 100% of the total flavonoid content [ 151 ]. Lastly, nutrient stress, salicylic acid, and cyclodextrin have also been applied as elicitors in Kalanchoe plants and cell suspension cultures, with the prediction of the best conditions by using new tools of machine learning [ 152 , 153 , 154 ].…”
Section: Why Choose Kalanchoe ? Singular Aspects O...mentioning
confidence: 99%